The Effect of Climate on Thermal Loads in Living Walls - Rosmina, Ahmad Bustami; Simon, Beecham; James, Hopeward; Martin, Belusko; Ahmad A. M, Khairulzaim (MDPI, 2025)
This study analysed the impact of living walls on energy-efficient residential buildings in major Australian cities with varying climates. The aim was to identify and quantify the shading and evapotranspiration benefits of living walls using calibrated thermal simulation software. Empirical correlations were applied to replicate the evapotranspiration effect in the simulation. Building dynamic thermal modelling was undertaken with the widely-used AccuRate Sustainability energy rating software. Two house designs were used in the simulation, applying various scenarios to assess the benefits of living walls in various Australian cities. The results showed that living walls provided the most cooling in warm and dry climates such as Perth and Adelaide, with minimal benefits in tropical regions such as Darwin. In temperate climates, living walls had little impact on heating, but in colder climates, they increased heating demand. Homes with insulated walls are common in modern residential construction. For such homes, the evapotranspiration effect rather than the shading or insulation characteristics of the living wall became the primary mechanism for reducing cooling loads, particularly in drier climates. When applying a single living wall for idealized models a potential cooling savings in cooling energy of 10–16% was determined, whereas for typical home designs this saving reduced to below 1%. It was found that the benefits of living walls are comparable to or lower than simpler, more cost-effective passive strategies such as adjusting building orientation or using light-coloured walls.